Signal transduction pathways and resistance to targeted therapies in glioma. (October 2019) - Tomiyama, Arata; Ichimura, Koichi
Abstract: Although surgical techniques and adjuvant therapies have undergone progressive development for decades, the therapeutic outcomes for treating glioblastoma (GBM) remain poor. The main reasons for the poor prognosis of gliomas are that limited tumor tissue that can be resected (to preserve brain functions) and that residual tumors are often resistant to irradiation and chemotherapy. Therefore, overcoming the resistance of residual tumors against adjuvant therapy is urgently needed for glioma treatment. Recent large cohort studies of genetic alterations in GBM demonstrated that both genetic information and intracellular molecular signaling are networked in gliomas and that such information may help clarify which molecules or signals serve essential roles in resistance against radiation or chemotherapy, highlighting them as potential novel therapeutic targets against refractory gliomas. In this review, we summarize the current understanding of molecular networks that govern glioma biology, mainly based on cohort studies or recent evidence, with a focus on how intracellular signaling molecules in gliomas associate with each other and regulate refractoriness against current therapy.